2022
DOI: 10.1088/1748-9326/ac8be8
|View full text |Cite
|
Sign up to set email alerts
|

Shocks, socio-economic status, and food security across Kenya: policy implications for achieving the Zero Hunger goal

Abstract: This study assessed the association between shocks, socio-economic factors, and household food security across Kenya, and provided policy implications for achieving the Zero Hunger goal at national and local levels in Kenya. We analysed the Kenya Integrated Household Budget Survey 2015-16 data for 24,000 households by employing regression models. Our multiple findings show that: (1) half of the surveyed population across Kenya were food insecure; (2) large disparities in food security status exist across the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Regarding the effect of climate change on food security, the studies by Islam et al (2022), Mekonnen et al (2021), Randell et al (2021), Erasto, (2021), and Randell et al, 2022 found that climate extremes negatively affect food security in Bangladesh, Ethiopia, Nepal, and Tanzania. Also, Mutea et al (2022) addressed shocks, socioeconomic status, and food security in Kenya, underscoring disparities and the impact of shocks on food security. Utonga et al (2023) highlighted institutional determinants in the Singida Region, Tanzania, emphasising the significant impact of institutions on food security.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effect of climate change on food security, the studies by Islam et al (2022), Mekonnen et al (2021), Randell et al (2021), Erasto, (2021), and Randell et al, 2022 found that climate extremes negatively affect food security in Bangladesh, Ethiopia, Nepal, and Tanzania. Also, Mutea et al (2022) addressed shocks, socioeconomic status, and food security in Kenya, underscoring disparities and the impact of shocks on food security. Utonga et al (2023) highlighted institutional determinants in the Singida Region, Tanzania, emphasising the significant impact of institutions on food security.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The above studies have provided insights regarding various aspects of food security, exploring different geographical locations and influencing factors. These studies indicate that the factors influencing food security include external factors such as the Russia-Ukraine conflict, which impacted those African countries negatively depend on food imports (Zainab, 2023;Enilolobo et al, 2023) (ii) agricultural imports and exports which influence the domestic market prices (Yilmaz & Njora, 2021); climate change-related factors (Mekonnen et al 2021;Islam et al, 2022;Randell et al 2021;Randell et al 2022); households characteristics such as household's dependent ratio and socio-economics status (Saruni et al, 2018;Mutea et al 2022), institutional factors (Utonga et al 2023), and agricultural policies (Yilmaz & Njora, 2021). While most studies have shown that food security is highly attributed by social and demographic factors little has been explored on term of women resource ownership particularly land and the effects of remittances.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%